2016
DOI: 10.1371/journal.pone.0166143
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia Influences the Effects of Sodium Channel Blocking Drugs in Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes

Abstract: IntroductionFever can increase the susceptibility to supraventricular and ventricular arrhythmias, in which sodium channel dysfunction has been implicated. Whether fever influences the efficacy of sodium channel blocking drugs is unknown. The current study was designed to investigate the temperature dependent effects of distinct sodium channel blocking drugs on the sodium currents in human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs).Methods and ResultshiPSC-CMs were generated from human sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…In this regard, heat stress is cytotoxic to cells and can induce many cellular changes, including a loss of cellular homeostasis. While there have been some reports on the effects of long-time hyperthermia in cells [21, 22], additional research is needed in the area of cell damage and cell signaling pathway after heat treatment in short time, which may be useful for the prevention or treatment of.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, heat stress is cytotoxic to cells and can induce many cellular changes, including a loss of cellular homeostasis. While there have been some reports on the effects of long-time hyperthermia in cells [21, 22], additional research is needed in the area of cell damage and cell signaling pathway after heat treatment in short time, which may be useful for the prevention or treatment of.…”
Section: Discussionmentioning
confidence: 99%
“…The hiPS cell lines were differentiated into cardiomyocytes as described in our previous studies [ 26 , 27 ]. Cardiomyocytes 30 to 60 days after the onset of differentiation were dissociated from 24-well plates and used for PCR analysis or plated as single cells on Matrigel-coated 3.5 cm petri dishes for patch clamp measurements.…”
Section: Methodsmentioning
confidence: 99%
“…This sodium channel blocker was tested in hiPS-CMs in our recent study to evaluate its effect on peak and late sodium channel currents. 22 Accordingly, the defined concentrations of 3, 10, and 30 μM were used in the current study. In all the tested concentrations, ajmaline did not change APA and APD50.…”
Section: Ajmalinementioning
confidence: 99%
“…Our group has successfully used human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) to model some key features of different diseases, including SQTS1. [22][23][24][25][26][27][28] We have demonstrated that the hiPSC-CMs from an SQTS1 patient (SQTS1 hiPSC-CMs) are able to recapitulate the single-cell phenotypic features of SQTS (APDshortening and arrhythmic calcium transients) and provide novel opportunities to further elucidate the disease mechanism and test drug effects. 27 Therefore, we designed the current study to examine the APDprolonging and antiarrhythmic effects of some drugs using our well-defined and characterized model of SQTS1.…”
mentioning
confidence: 99%
See 1 more Smart Citation